Issues and possible solutions in cognitive diagnosis modeling applications: The case of a large-scale educational assessment in Mexico - Escudero, Scarlett; Vázquez-Lira, Ramsés; Leenen, Iwin; Sorrel, Miguel A. (Anales de Psicología / Annals of Psychology, 2026)
Cognitive diagnosis modeling (CDM) is a proposed framework for the creation and analysis of measurement tools that originated in the field of education and have extended to other areas of interest in psychology. These models have received a lot of attention in recent years, resulting in an abundance of theoretical contributions. However, there is still a shortage of studies applying these methodologies to real data. It is essential to evaluate the procedures in their natural context of application and to provide solutions tailored to the problems that may arise in practice. The purpose of this study is to apply CDM to a large-scale evaluation that assesses high school teachers in Mexico, which was designed based on a CDM framework. Five issues are identified that arose in the analysis of these data and provide guidelines on how to explore and find solutions to these issues with implementation in R. Besides discussing psychometric solutions, this paper also emphasizes the importance of consulting with content experts. By highlighting potential challenges that can arise even when all necessary elements for a large-scale CDM educational assessment are in place, this study aims to guide future empirical applications and methodological proposals.